ANALISIS EFEKTIVITAS PENDAMPINGAN KONSULTAN PAJAK DALAM PENYELESAIAN KASUS PERPAJAKAN KLIEN : STUDI KASUS KJA LLILIS ARDINI BOJONEGORO - Aliefah, Nur Azizatul; Djasuli, Mohamad (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2024)
This study aims to analyze the effectiveness of tax consultant assistance in resolving client tax cases at the Accounting Services Office (KJA) in Bojonegoro. This qualitative research uses a case study approach at KJA Lilis Ardini. Using qualitative data analysis, it was found that tax consultants have an important impact on clients in resolving tax problems, such as late payment and tax reporting. Key factors that affect the effectiveness of tax consultant assistance include the mentoring routine, good cooperation between consultants and clients, client honesty, and client awareness of the importance of tax compliance. The success of resolving tax cases is measured by the absence of complaints from the Tax Office   and the sustainability of the client-consultant partnership. Although it has only been operating for one year, KJA Lilis Ardini has shown consistency in providing effective services to clients, without any significant changes in the approach or strategy used